Program Database Elektronik Rekam Medis Pasien di Puskesmas Kapau, Kecamatan Tilatang Kamang, Kabupaten Agam - Fitrialny, Resty; Ardoni, Ardoni (Ilmu Informasi Perpustakaan dan Kearsipan, 2013)
This paper discusses electronic database of medical records of patients in Health Center Kapau, Tilatang Kamang Subdistrict, Agam Regency. This study aims to describe the design method of the database that is hoped can accelerate the performance of the Healt Center officer. Data were collected through observation and document reviews and then analyzed descriptively. Based on analysis of the data, it can conclude that in the database could be designed by using Microsoft Office Access 2007, a database application computer program for designing, creating and processing different types of data with a large capacity. This database consists of two tables, namely the identity of the patient table and patient visits table. In this database design typography and colors is used according to the needs of visible. Interesting, and easy to be read. Patient medical records database is especially useful for the health center since it can facilitate the work of officers inÂ  searching for the location of patientâ€™s medical record document. Moreover, the database can shorten working time of the officers because it can be retrieved quickly compared with the manual searching that relatively slow and takes a long time. Keywords: medical record; database; Microsoft Office Access